2020
DOI: 10.1093/jamia/ocaa082
|View full text |Cite
|
Sign up to set email alerts
|

Can Unified Medical Language System–based semantic representation improve automated identification of patient safety incident reports by type and severity?

Abstract: Objective The study sought to evaluate the feasibility of using Unified Medical Language System (UMLS) semantic features for automated identification of reports about patient safety incidents by type and severity. Materials and Methods Binary support vector machine (SVM) classifier ensembles were trained and validated using balanced datasets of critical incident report texts (n_type = 2860, n_severity = 1160) collected from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Due to the high volume of data collected by the IT systems responsible for these purposes, using free text for reporting these events reduces its effectiveness due to the difficulty in aggregating the data [ 86 ]. Of the 36 articles included in this systematic review, 13 [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 47 , 48 , 49 , 50 , 51 , 53 ] investigate the applications of AI to improve the efficiency of incident reporting systems. The studies predominantly focus their attention on the possibility of standardizing events according to their type and severity.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high volume of data collected by the IT systems responsible for these purposes, using free text for reporting these events reduces its effectiveness due to the difficulty in aggregating the data [ 86 ]. Of the 36 articles included in this systematic review, 13 [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 47 , 48 , 49 , 50 , 51 , 53 ] investigate the applications of AI to improve the efficiency of incident reporting systems. The studies predominantly focus their attention on the possibility of standardizing events according to their type and severity.…”
Section: Resultsmentioning
confidence: 99%
“…Empty reports were excluded, and text was changed into lower case. To provide informative features for classification, word tokenization, removal of stop words, stemming and lemmatization were applied [8].…”
Section: Data Collection Annotation and Pre-processingmentioning
confidence: 99%
“…Text classifiers driven by ML methods have been shown to be feasible for identifying events about a variety of patient safety problems such as falls and medication errors [7][8][9][10]. We have previously demonstrated the feasibility of using text classification to identify safety events involving health IT from MAUDE [11].…”
Section: Introductionmentioning
confidence: 99%
“…31 Wang et al determined that use of the UMLS could improve automated categorization of patient safety incident reports. 32 Rasmy et al found the UMLS useful in representing electronic health record (EHR) data in predictive modeling. 33 Bitton et al mapped transliterated terms to UMLS concepts to improve retrieval in a Hebrew online health community, 34 an example of using the UMLS both to extract information from social media and to aid interpretation of non-English text.…”
Section: Applications Of the Umls To Specific Problemsmentioning
confidence: 99%